Optimizing RhD Immune Globulin Use in Pregnancy - Miller, Elizabeth; El-Kassis, Lana; Saade, George; Horgan, Rebecca (American Journal of Perinatology, 2025)
The global shortage of RhD immune globulin, formally acknowledged by the Food and Drug Administration in 2023, is ongoing but has improved in recent months. In response, the American College of Obstetricians and Gynecologists (ACOG) issued guidance in March 2024 on alternative strategies to conserve RhD immune globulin supplies. Our objective is to evaluate strategies for optimizing RhD immune globulin use in pregnancy amidst a global shortage.This clinical opinion reviews guidance on strategies to conserve RhD immune globulin. These include targeted administration based on non-invasive fetal RhD genotyping using cell-free DNA (cfDNA), the use of alternative RhD immune globulin products, and selective withholding of prophylaxis in early pregnancy loss under 12 weeks' gestation. ACOG guidance on the administration of RhD immune globulin in pregnancy differs from many countries worldwide, as well as the World Health Organization and the American Society of Family Planning.Targeted administration and the use of non-invasive cell-free DNA (cfDNA) testing for fetal RhD status have shown promising accuracy and reliability in studies across multiple countries, leading to reduced unnecessary prophylaxis and potential cost savings. Additionally, withholding RhD immune globulin in select early pregnancy losses could further conserve resources without increasing alloimmunization risk.This review underscores the need for evidence-based approaches to manage limited RhD immune globulin supplies effectively and suggests that targeted prophylaxis could benefit both patient outcomes and healthcare resource allocation in the face of global shortages.
Keywords: rhogam; RhD immune globulin; rhesus negative; cfDNA; hemolytic disease of the fetus; alloimmunization; fetal antigen